2014
DOI: 10.1007/s15010-014-0690-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of EBV, HHV-6 and CMV DNA in the gastrointestinal tract of HIV-positive patients

Abstract: Human herpes viruses (HHVs) have been frequently detected in the gastrointestinal (GI) tract and may contribute to the development of gastric cancer. In the present study, the detection rate and viral load of Epstein Barr virus (EBV), HHV-6 and Cytomegalovirus (CMV) were assessed in the GI tract of human immunodeficiency virus (HIV) positive patients and of uninfected patients. The analysis revealed a significantly higher detection rate of EBV and HHV-6 in HIV-infected individuals than in uninfected subjects (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…[47] HCMV reactivation occurs in patients with immunosuppression of diverse etiology [48,49] and in organ donors or recipients, [50] among others. In 18 HIV-positive dyspeptic patients, Falasca et al [51] found anti-HCMV IgG antibodies but in none of them, HCMV DNA was detected in antral biopsies. On the other hand, gastritis cases caused by HCMV have been reported in immunocompetent patients [52] and gastric cancer cases that have evolved from HCMV gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…[47] HCMV reactivation occurs in patients with immunosuppression of diverse etiology [48,49] and in organ donors or recipients, [50] among others. In 18 HIV-positive dyspeptic patients, Falasca et al [51] found anti-HCMV IgG antibodies but in none of them, HCMV DNA was detected in antral biopsies. On the other hand, gastritis cases caused by HCMV have been reported in immunocompetent patients [52] and gastric cancer cases that have evolved from HCMV gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal cancer (GIC) typically develops from a benign polyp, becomes an adenoma, and finally transforms into a carcinoma ( 134 ). One study detected HHV-6 in the GI tract of 63% of healthy individuals ( 135 ), whereas another study detected HHV-6 in 23% of liver transplant patients and 19% of immunocompetent patients ( 136 ). HHV-6 causes a range of GI symptoms, including diarrhea, colitis, and bacterial infection of the digestive tract ( 137 ), and an association between biliary complications and HHV-6 has been reported in many studies ( 136 , 138 ).…”
Section: Hhv-6 As the Sole Infectious Agent In Cancers: By System/sitmentioning
confidence: 99%
“…Like other herpes viruses, HHV-6 establishes lifelong latency in the host and may reactivate under conditions of impaired immunity. 294 Most severe HHV-6 infections occur in markedly immunocompromised children or adults 294 including HCT [322][323][324][325] or SOT recipients [326][327][328][329] ; or those with congenital or acquired immunodeficiency disorders, 296,330 HIV, 312,331 or lymphomas or hematological malignancies receiving chemotherapy. 293,324,332 Among HCT recipients, asymptomatic HHV-6 DNAemia is common (30-60%), 300,325,333,334 but the vast majority of infections are self-limited and do not require treatment.…”
Section: Reactivation Of Hhv-6 In Immunocompromised Hostsmentioning
confidence: 99%